ExCeL: combining extrusion printing on cellulose scaffolds with lamination to create in vitro biological models. (1st April 2019) - Shahin-Shamsabadi, Alireza; Selvaganapathy, P Ravi
Abstract: Bioprinting is rapidly developing into a powerful tool in tissue engineering, for both organ printing and the development of in vitro models that can be used in drug discovery, toxicology and in vitro bioreactors. Nevertheless, the ability to create complex 3D culture systems with different types of cells and extracellular matrices integrated with perfusable channels has been a challenge. Here we develop an approach that combines the xurography of a scaffold material (cellulose) with extrusion printing of bioinks onto it, followed by assembly in a layer-by-layer fashion to create complex 3D culture systems that could be used as in vitro models of biological processes. This new method, termedExCeL, can recapitulate the complexities of natural tissues with a proper 3D distribution of cells, extracellular matrices, and different molecules, while providing the whole structure with mechanical stability, and direct and easy access to the cells, even the ones that are positioned deep in the bulk of the structure, without the need to fix or section the samples. Briefly, the bioprinting of predefined patterns with a feature size of ∼1 mm has been made possible by treating paper with the hydrogel's crosslinker and printing cell-embedded hydrogel that will solidify immediately upon contact with the paper. These impregnated layers can be used as single layers or in a layer-by-layer approach by stacking them (here up to four layers) for applications such as cell migration and proliferation in 3D structures composed of collagen or alginate. Cells are generally sensitive to the amount of FBS in their culture media and we have shown how FBS amount will effect cell migration. By cutting the paper in certain patterns, printing hydrogel on the remaining parts of it, and stacking the paper in layers, features like embedded channels are formed that will provide cells will better mass transfer in thick structures. This technique provides biologists with a unique tool to perform sophisticated in vitro assays.